Sensing the optical properties of diffusive media by acousto-optic pressure contrast imaging - Lai, P; Roy, R; Murray, T (Society of Photo-optical Instrumentation Engineers, 2009)
Acousto-optic imaging (AOI) is a dual-wave modality that combines ultrasound with diffuse light to achieve deep-tissue imaging of optical properties with the spatial resolution of ultrasound. Progress has been made in the detection of optically absorbing inhomogeneities in recent years, yet it remains a challenge for AOI to detect targets possessing low scattering contrast and to obtain quantitative measurement of optical properties at depth with high resolution. A new photorefractive crystal (PRC) based AOI system operating in the near-infrared optical wavelength was developed and optimized. Based on relative changes in the AOI response induced by different acoustic pressures, we now propose a new sensing and imaging modality, pressure contrast imaging (PCI), to enhance and quantify the detection of scattering inhomogeneities. It is demonstrated experimentally that the image contrast information obtained with the new approach is independent of the background light intensity and the details of the optical collection components and potentially allows for an accurate and quantitative characterization of the media's spatially dependent optical properties.